Examining the validity of the Lexical Access Time Test (LEXATT2) - Tatsuo Iso (Vocabulary Learning and Instruction)
This study aimed to investigate the validity of the Lexical Access Time Test (LEXATT2). The first step was to examine the test results to determine if it was able to differentiate between participants with different English proficiency levels. The results were further analyzed to see if longer target words elicited slower lexical access times. The results of the 119 participants indicated promise in that LEXATT2 established an ability to distinguish proficiency levels to some extent. Further, it was found that LEXATT2 elicited slower lexical access time from the participants with lower English proficiency.